2021
DOI: 10.1093/ecco-jcc/jjab046
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccination in IBD: Past Lessons, Current Evidence, and Future Challenges

Abstract: Since the beginning of the pandemic, patients with inflammatory bowel diseases (IBD) have been considered at high-risk for infection and complications of COVID-19. However, IBD patients and patients taking immunosuppressive therapy were excluded from clinical phase III vaccine trials, complicating the assessment of effectiveness of these new vaccines. From past experience we know that adapted vaccination strategies may be appropriate in some IBD patients to optimize immunogenicity. We review current evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 97 publications
0
30
0
2
Order By: Relevance
“…3 A study showing attenuated antinucleocapsid responses to SARS-CoV-2 infection in IBD patients on infliximab and another study reporting poor antispike antibody responses in organ transplant patients after the first dose of messenger RNA vaccines have raised concern regarding vaccine responses in IBD patients. [4][5][6] Still, the impact of medications on COVID-19 vaccine efficacy in IBD patients is unknown, because patients with immunosuppressed states and/or treated with immunosuppressants were excluded from vaccine trials. To address this, we evaluated serologic responses to COVID-19 vaccination with the SARS-CoV-2 spike (S) messenger RNA BNT162b2 (Pfizer-BioNTech) and messenger RNA-1273 (National Institutes of Health [NIH]-Moderna) vaccines in IBD patients.…”
mentioning
confidence: 99%
“…3 A study showing attenuated antinucleocapsid responses to SARS-CoV-2 infection in IBD patients on infliximab and another study reporting poor antispike antibody responses in organ transplant patients after the first dose of messenger RNA vaccines have raised concern regarding vaccine responses in IBD patients. [4][5][6] Still, the impact of medications on COVID-19 vaccine efficacy in IBD patients is unknown, because patients with immunosuppressed states and/or treated with immunosuppressants were excluded from vaccine trials. To address this, we evaluated serologic responses to COVID-19 vaccination with the SARS-CoV-2 spike (S) messenger RNA BNT162b2 (Pfizer-BioNTech) and messenger RNA-1273 (National Institutes of Health [NIH]-Moderna) vaccines in IBD patients.…”
mentioning
confidence: 99%
“…However, there is limited information about how biological therapy with immunosuppressive medication will influence the immune response during COVID-19 vaccination of IBD patients [4,14]. Wellens et al (2021) showed that humoral and cellular immune response in IBD could be impaired after some vaccines…”
Section: Discussionmentioning
confidence: 99%
“…Despite these concerns, vaccine effectiveness seems to be the key concern, rather than safety. All the entities and experts recommend COVID‐19 vaccination for IBD patients, 151 , 152 , 153 , 154 , 155 including those who had anaphylaxis following biologic treatment. 151 …”
Section: Covid‐19 Vaccines: Where Are We Now?mentioning
confidence: 99%